The effects of kicking leg preference on balance ability in elite soccer players - Fletcher, I. M.; Long, C. S. (Journal of Athletic Enhancement, 2013)
Soccer has a high number of lower limb non-contact injuries, with leg asymmetry linked to this injury occurrence. Screening for balance deficits is used as a predictor of potential injury; therefore the aim of this study was to determine whether static and dynamic balance differs in elite soccer players preferred kicking and nonpreferred kicking legs. Fifteen male professional soccer players were tested for static balance; standing on one leg, and dynamic balance, a hop and hold task and a kicking task. Balance ability was assessed by measuring centre of pressure deviation. Results indicated that static balance and hop and hold tests were not significantly different (p>0.05) when dominant and non-dominant kicking legs were compared. The kicking balance task indicated a significant increase (p = 0.05) in balance ability for the player`s nondominant limbs. Further, left sided players had significantly better (p = 0.05) dominant leg balance when compared to right sided players. These findings suggest that the static and dynamic balance tasks employed in this study were not specific enough to establish possible balance asymmetries in professional elite soccer players, while the passing dynamic balance test seems to be sensitive enough to show dominant and non-dominant leg discrepancies. It is therefore suggested that balance tasks, used to screen players, need to mimic the actions linked to injuries within soccer in order to explore dominant and non-dominant asymmetry.